Habitants des bidonvilles et revendications de droits de citoyenneté au Maroc - Jaouad Agudal (L’Année du Maghreb)
Scholarship has shown that, in moroccan shantytowns, the rights of citizenship hold an important place in practices and narratives of the inhabitants. Based on fieldwork conducted in shantytowns in different regions (Nzala Raddaya – in the Fes-Meknes region) and Douar Laamour (in the Casablanca-Settat region), the author paid special attention to the importance taken on by administrative documents which vouch for the status of shantytown dwellers. As such, these documents enable their holders to benefit from resettlements policies in the aim of eradicating shantytowns. The materiality of these documents, which grant access to public services through to the possibility of resettlement, are at the heart of strategies, enacted both by the shantytown inhabitants and by the civil servants who deliver or claim them.